2020
DOI: 10.3389/fmolb.2020.589435
|View full text |Cite
|
Sign up to set email alerts
|

Proteome of the Triatomine Digestive Tract: From Catalytic to Immune Pathways; Focusing on Annexin Expression

Abstract: Rhodnius prolixus, Panstrongylus megistus, Triatoma infestans, and Dipetalogaster maxima are all triatomines and potential vectors of the protozoan Trypanosoma cruzi responsible for human Chagas’ disease. Considering that the T. cruzi’s cycle occurs inside the triatomine digestive tract (TDT), the analysis of the TDT protein profile is an essential step to understand TDT physiology during T. cruzi infection. To characterize the protein profile of TDT of D. maxima, P. megistus, R. prolixus, and T. infestans, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 177 publications
0
26
0
Order By: Relevance
“…It is noteworthy to mention that although proteins associated with IMD, Toll, and Jak/STAT pathways involved in innate immunity have been identified in R. prolixus digestive tract proteomes [ 20 , 95 , 96 ], the early events post blood feeding resume in the induction of these very few immune-related proteins. Although lysozymes have been suggested to have a role in immunity, the observed up-regulation in the early hours post blood ingestion supports their digestive function.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy to mention that although proteins associated with IMD, Toll, and Jak/STAT pathways involved in innate immunity have been identified in R. prolixus digestive tract proteomes [ 20 , 95 , 96 ], the early events post blood feeding resume in the induction of these very few immune-related proteins. Although lysozymes have been suggested to have a role in immunity, the observed up-regulation in the early hours post blood ingestion supports their digestive function.…”
Section: Discussionmentioning
confidence: 99%
“…This enzyme catalyzes the synthesis of esterified cholesterol and lysophosphatidylcholine from cholesterol and phosphatidylcholine ( Ossoli et al, 2016 ), and it is present in the rabbit blood used for insect feeding ( Carlucci et al, 2012 ). A recent proteomic analysis of R. prolixus midgut showed that enzymes involved with lipid utilization are highly expressed in this organ, confirming that it is very active in terms of lipid metabolism ( Gumiel et al, 2020 ). Thus, an alternative explanation may be the excretion of esterified cholesterol synthesized by the intestinal cells.…”
Section: Discussionmentioning
confidence: 82%
“…For instance, the relative abundance of gut bacterial community in T. sordida varied greatly among the anterior and posterior midgut, and hindgut 43 . The protein profile expression of T. infestans digestive tract seems to be affected by the ingestion of blood meal 44 . The varying chemical profile is expected to be reflected in the spectral signature and could overlap with the presence of the pathogen.…”
Section: Discussionmentioning
confidence: 99%